Analisis Strategi Bisnis UMKM Jambi â€œWonderfulplan.Jasadekorâ€ dengan Metode Business Model Canvas (BMC) - Jamira, Anaseputri; Asmas, Denny (Universitas Batanghari Jambi, 2024)
This research aims to answer the problem of how to describe the Business Model and Business Strategy Analysis of UMKM Jambi